Membangkitkan Jiwa Kewiraushaan Di Kalangan Milenial Berbasis Pengelolahan Limbah Yang Ramah Lingkungan Di MAN 1 Kota Bengkulu - Astuty, Kamelia; Wijaya, Ermy; Putri, Lydia Gustina; Nurzam, Nurzam; Anzori, Anzori (Jurnal Dehasen Untuk Negeri, 2024)
Proper waste management must be instilled in children from an early age. The purpose of this writing is to explain the definition of waste, the impact of waste and the management that has been carried out by the government and waste management in one of the MAN 1 Schools in Bengkulu City. This service discusses generating an entrepreneurial spirit among millennials based on environmentally friendly waste processing, especially waste management. Proper waste management is carried out with the 3R pattern (Reduce, Reuse and Recycle) with the application to increase awareness about the environment (awareness), increase deep thinking about the environment (Thinking) and carry out waste management to increase the economic value and aesthetic value of waste (doing). The application of the waste management pattern appropriately increases the entrepreneurial spirit among the MAn 1 community environment in Bengkulu city.